2015
DOI: 10.1111/jmcb.12228
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting National Recessions Using State‐Level Data

Abstract: Abstract:A large literature studies the information contained in national-level economic indicators, such as financial and aggregate economic activity variables, for forecasting U.S. business cycle phases (expansions and recessions.) In this paper, we investigate whether there is additional information regarding business cycle phases contained in subnational measures of economic activity. Using a probit model to predict the NBER expansion and recession classification, we assess the forecasting benefits of addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Finally, a handful of papers have applied methods similar to those used here to identify or forecast recessions. Owyang et al () use a Bayesian model‐averaging methodology to show that state‐level employment data identify turning points in the national economy. Giusto & Piger () use machine‐learning algorithms to evaluate how quickly one can call a recession in real time.…”
Section: Empirical Setupmentioning
confidence: 99%
“…Finally, a handful of papers have applied methods similar to those used here to identify or forecast recessions. Owyang et al () use a Bayesian model‐averaging methodology to show that state‐level employment data identify turning points in the national economy. Giusto & Piger () use machine‐learning algorithms to evaluate how quickly one can call a recession in real time.…”
Section: Empirical Setupmentioning
confidence: 99%
“…Many studies now use a variety of methods, including MIDAS (Ghysels, Santa‐Clara and Valkanov 2004; Ghysels, Hill and Motegi 2016), dynamic factor models (Giannone, Reichlin and Small 2008; Aastveit and Trovik 2012; Chernis and Sekkel 2017; Dahlhaus, Guénette and Vasishtha 2017; Bragoli and Fosten 2018), and even an amalgamation of the two—factor MIDAS (Marcellino and Schumacher 2010). These have been complemented by approaches drawing on Bayesian techniques (Owyang, Piger and Wall 2015; Bok et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Forecasting National-Level Macroeconomic IndicatorsHernández-Murillo andOwyang (2006) and Owyang, Piger and Wall (2015), among others, showed that regionally-disaggregated data can predict national-level data. Here, we consider whether state-level data predicts national-level payroll employment 18. Because national-level data are (typically) not exactly equal to the sum of the state-level data, we level the playing …eld by replacing the BEA's reported national series with the sum of the state-level data-in this case, state-level payroll employment 19.…”
mentioning
confidence: 99%